Congenital Pseudarthrosis of the Tibia. Issue 4 (2017) - O'Donnell, Courtney; Foster, James; Mooney, Ryan; Beebe, Corey; Donaldson, Nathan; Heare, Travis
Abstract : Patients with congenital pseudarthrosis of the tibia do not have a normal tibia. In such patients, the entire tibia is abnormal (even outside of the established pseudarthrosis site); the bone does not have a normal healing response to injury or osteotomy, and the proximal growth plate typically has an abnormal inclination. Operative attempts to promote union at the pseudarthrosis site (intramedullary nailing with bone-grafting, the Ilizarov technique, and microvascular free fibular transfer) fail to address the abnormal tibia as a whole. We must critically evaluate treatment outcomes for patients with congenital pseudarthrosis of the tibia; the definition of a good result must include patient-related outcome scores rather than simply radiographic union. There is need for prospective Level-I studies to compare surgical treatment options with the addition of health-related quality-of-life scores. Amputation should be viewed as a viable treatment option rather than a surgical failure. The achievement of a healed, straight extremity by skeletal maturity, with as few surgical procedures as possible, is essential for a child with congenital pseudarthrosis of the tibia. The extremity must be strong enough to allow the patient to function with no activity restrictions, regardless of whether the treatment course has been limb preservation or amputation.